Qualidade na educação infantil em instituições brasileiras: contributos de pesquisas acadêmicas para o debate - Oliveira, Daniele Ramos de [UNESP]; Guimarães, Célia Maria [UNESP]; Lima, Elieuza Aparecida de [UNESP] (My University, 2013)
This article presents elements that make up the quality of education in the age group of zero to five years, offered by institutions of Early Childhood Education in Brazil, based on research results disseminated in theses and dissertations that focus on this theme. It was used as the methodological procedure outlined mapping Brazilian literature of academic research related to the Post-Graduate Education, which focus on the issue in the period between 1996 and 2012. The results of the study provide insights on funding, teacher training, family, quality of care in the school systems, institutional assessment, perceptions of quality and educational practices that allow discuss the quality of early childhood education offered in Brazilian institutions. Moreover, considering that not convenient to take the concept of quality of early childhood education as universal as this is linked to the context, the conceptions about children and their education.

O presente artigo apresenta elementos que compõem a qualidade da educação na faixa etária de zero a cinco anos, oferecida por instituições de Educação Infantil no Brasil, com base nos resultados de pesquisa disseminados em teses e dissertações que enfocam essa temática. Foi utilizado o procedimento metodológico delineado como mapeamento bibliográfico das pesquisas acadêmicas brasileiras vinculadas aos Programas de Pós-Graduação em Educação, os quais focalizam a questão no período entre 1996 e 2012. Os resultados dos estudos fornecem elementos sobre financiamento, formação de professores, família, qualidade do atendimento em redes de ensino, avaliação institucional, percep- ções sobre qualidade e práticas educativas que permitem discutir sobre a qualidade da Educação Infantil oferecida nas instituições brasileiras. Além disso, considera-se que não convém tomar o conceito de qualidade da Educação Infantil como universal, visto que este se vincula ao contexto, às concepções sobre criança e à sua educação.
Quality in early childhood education in brazilian institutions: academic research contributions to the debate
Keywords: educação infantil; qualidade